EYE DISEASE INFORMATION APPLICATION PROGRAM USING MICROSOFT VISUAL BASIC 6.0 - Devy Afiani; Marzuki, SKom, MMSI Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2007)
This scientific writing, discusses about how to make an eye disease information usingMicrosoft Visual Basic 6.0. Information can be interpreted as a computer softwarethat has a knowledge base for a particular domain and using inference reasoningresembles an expert in solving a problem. Where this information when linked to theability of doctors to diagnose the health condition of patients at an early stage, we cancreate an assigned computer system identify and analyze patients' symptoms and thenprovide recommendations directly to the patient.Models made in implementing the information into an application program. Thisapplication was made aiming to help us in the early diagnosis of eye diseases. And tomake it easier to serve our patients without the patient must leave the house. Which inaddition to consuming time, effort and cost but also dangat feared conditions. Withthis program can reduce the duty of a doctor and are not directly replace the absenceof a doctor.